A new species of Trichosalpinx (Orchidaceae: Pleurothallidinae) from Costa Rica - Fernández Campos, Melania (2013)
Trichosalpinx sanctuarii, a new species of Orchidaceae, subtribe Pleurothallidinae, is described and illustrated. It most resembles T. ringens, from which it is distinguished in the text. The new species is endemic to Costa Rica.